Isolation of five Enterobacteriaceae species harbouring blaNDM-1 and mcr-1 plasmids from a single paediatric patient - Martino, Florencia (2019)
In Argentina, NDM metallo-β-lactamase was first reported in 2013. By now, it has disseminated throughout the country in diverse Gram negative bacteria. Here, we report the case of a paediatric patient that underwent a 1-year hospitalisation due to erythrodermic psoriasis in 2014 and received multiple antimicrobial treatments. During his stay, five isolates were obtained from rectal swabs (rs) or blood culture (bc) suspicious of carbapenemase production: a K. quasipneumoniae subsp. quasipneumoniae (rs), Citrobacter freundii (rs), Escherichia coli (bc), Enterobacter cloacae (rs), and a Serratia marcescens (bc). The isolates were studied with broth microdilution, biparental conjugation and plasmid and whole genome sequencing (Illumina). All isolates harboured an 138,998-bp type 1 IncC plasmid that carried blaNDM-1, bleMBL, blaCMY-6, rmtC, aac(6’)-Ib, and sul1 resistance genes. Additionally, the blaNDM-plasmids contained ISKpn8 an insertion sequence previously described as associated only to blaKPC. One isolate, a colistin-resistant E. coli, also carried a mcr-1-containing an IncI2 plasmid, which did not harbour additional resistance. The whole genome of K. quasipneumoniae subsp. quasipneumoniae isolate was fully sequenced. This isolate harboured, additionally to blaNDM, three plasmid-mediated quinolone resistance genes: qnrB4, qnrB52 and aac(6’)-Ib-cr1. The E. cloacae isolate also harboured qnrA1. These findings alert to the underestimated horizontal dissemination of multidrug-resistant plasmids limiting treatment options with last resort antimicrobials.